Agile Manufacturing: A Hybrid Systematic Literature Review and Bibliometric Analysis - Suwandi (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2026)
Agile manufacturing has become an increasingly important capability in contemporary manufacturing environments characterized by rapid technological change, global competition, and operational uncertainty. Despite the growing interest in agility-related research, studies on agile manufacturing remain fragmented and are predominantly concentrated in developed countries. This study aims to systematically review and map the development of agile manufacturing research through a hybrid approach combining Systematic Literature Review (SLR) and bibliometric analysis. Data were collected from the Scopus database using agile manufacturing-related keywords in titles, abstracts, and keywords. The selected articles were screened based on predefined inclusion and exclusion criteria following the PRISMA framework. Bibliometric analysis was conducted using VOSviewer to identify publication trends, influential authors, institutional affiliations, country contributions, and keyword co-occurrence networks. The findings indicate that agile manufacturing research has experienced significant growth, particularly during the Industry 4.0 era, with major contributions originating from India, the United States, and the United Kingdom. The keyword network highlights strong associations among agile manufacturing systems, lean production, Industry 4.0, manufacturing systems, and dynamic capabilities. However, research remains largely focused on technological and operational dimensions, while human-centered and context-specific studies, particularly in emerging economies such as Indonesia, are still limited. This study contributes to the literature by providing a comprehensive overview of the intellectual structure of agile manufacturing research and identifying future research opportunities related to workforce agility, sustainability, digital transformation, and organizational resilience. The findings offer valuable insights for researchers and practitioners seeking to enhance manufacturing competitiveness and adaptability in dynamic industrial environments.